2013
DOI: 10.3389/fpls.2013.00379
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transplant size on the above- and below-ground performance of four contrasting field-grown lettuce cultivars

Abstract: Background and aims: Modern lettuce cultivars underperform under conditions of variable temporal and spatial resource availability, common in organic or low-input production systems. Information is scarce on the impact of below-ground traits on such resource acquisition and performance of field-grown lettuce; exploring genetic variation in such traits might contribute to strategies to select for robust cultivars, i.e., cultivars that perform well in the field, even under stress.Methods: To investigate the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
(20 reference statements)
0
24
1
Order By: Relevance
“…When N stress occurs in a transplanted lettuce crop in the upper soil layer (0-20 cm), roots can elongate and increase root length density at deeper soil layers to capture more N (Kerbiriou et al 2013a). Kerbiriou et al (2013b) showed that lettuce cultivars with higher root weight and rooting depth resulted in higher yields. However, one of the tested cultivars had the highest physiological use efficiency (g dry matter produced per g N accumulated in the head) and gave the most stable yield across trials despite a relatively small root system.…”
Section: Lettucementioning
confidence: 99%
“…When N stress occurs in a transplanted lettuce crop in the upper soil layer (0-20 cm), roots can elongate and increase root length density at deeper soil layers to capture more N (Kerbiriou et al 2013a). Kerbiriou et al (2013b) showed that lettuce cultivars with higher root weight and rooting depth resulted in higher yields. However, one of the tested cultivars had the highest physiological use efficiency (g dry matter produced per g N accumulated in the head) and gave the most stable yield across trials despite a relatively small root system.…”
Section: Lettucementioning
confidence: 99%
“…Nitrate content (soil [NO 3 ], assessed in ppm) in each 0.1 m soil layer was measured using an Ion Selective Electrode (ThermoFisher™, Waltham, MA, USA) using the method described previously by Sibley et al ( 2009 ) and also used in Kerbiriou et al ( 2013a ).…”
Section: Methodsmentioning
confidence: 99%
“…Kerbiriou et al ( 2014 ) showed that in lettuce the relationship between root mass and nitrate capture does not follow the relationship found by King et al in barley (King et al, 2003 ), where the non-captured resource logarithmically declines with an increase in the amount of roots or with the root length density. Although nitrate capture in lettuce is generally fairly correlated to root mass or root length density when field conditions are conducive to growth (Kerbiriou et al, 2013a ), in lettuce localized root growth is related to specific, localized resource availability as demonstrated by Kerbiriou et al ( 2013b ) in a pot trial. In case localized nitrate shortage was applied, root growth was more abundant in N rich soil layers—as previously noted by Hodge ( 2004 ) in grass species under various conditions—whereas when localized drought was applied, root growth occurred in the dry compartment (as opposed to the moist compartment).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Kerbiriou et al (2013) provides first evidence that “robustness” and head growth rates of lettuce cultivars are related to the size of the root system. Terzaghi et al (2013) investigated C and N concentrations in Fagus sylvatica fine roots in relation to different stand characteristics resulting from conversion of coppiced forests to high forests.…”
mentioning
confidence: 99%